2018
DOI: 10.1515/hmbci-2017-0075
|View full text |Cite
|
Sign up to set email alerts
|

Neck adipose tissue – tying ties in metabolic disorders

Abstract: Upper body adipose tissue accumulation has been associated with clustering of metabolic disorders and increased cardiovascular risk. Neck circumference (NC) indicated that subcutaneous adipose tissue (SAT) in that region is an independent pathogenic depot that might account for the additional risk missed by visceral adipose tissue (VAT). Neck adipose tissue (NAT) is not only one more ectopic depot but has several particular features that might modulate its metabolic role. Besides a controversial impact on obst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…Our results extend previous findings that underlined (the fact) that NC has as a simple and practical indicator of adiposity 21,39 and is positively associated with VAT measured with MRI and CT 16,17,25,40 . In addition, we observed that, after adjusting for age, NC, BMI, WC, FM, and FMI remained significant predictors of VAT.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results extend previous findings that underlined (the fact) that NC has as a simple and practical indicator of adiposity 21,39 and is positively associated with VAT measured with MRI and CT 16,17,25,40 . In addition, we observed that, after adjusting for age, NC, BMI, WC, FM, and FMI remained significant predictors of VAT.…”
Section: Discussionsupporting
confidence: 90%
“…However it should be underscored the role of intermuscular depots of fat located in the thigh as a relevant predictor of cardiometabolic risk factors in adults who are normal, overweight or obese 11,41 . Taken together, these findings uncover the potential role of NC as a subrrogate of a patogenic neck adipose tissue due to a greater flow of systemic free fatty acids (FFA), that could partly explain the cardiometabolic risk missed by VAT 17,40 . In fact, previous evidence has showed that elevated FFA concentrations reproduce the metabolic abnormalities of obesity and that the upper body fat increased in women with obesity would be the most important contributor in the systemic FFA release 42 .…”
Section: Discussionmentioning
confidence: 90%
“…For the latter, these adipose tissue samples were excised from patients undergoing neck surgery for malignancies or nodular goitre 5 . It is important to note that adipose tissue from the neck region are inherently different from most other adipose depots [6][7][8] . The neck region is primarily where the browning mechanism was disclosed and beside the UCP1 positive cells, it contains at least two types of adipocytes originating from two distinct mesenchymal stem cell lineages.…”
Section: Differences In the Site Of Adipose Explant Collection And CLmentioning
confidence: 99%
“…The neck region is primarily where the browning mechanism was disclosed and beside the UCP1 positive cells, it contains at least two types of adipocytes originating from two distinct mesenchymal stem cell lineages. The classic brown adipocytes with precursors in common with muscle cells and newly recognized beige adipocytes which have the same precursor as white adipose cells 7 . This unique aspect of neck adipose tissue should be should be taken into consideration when interpreting the results.…”
Section: Differences In the Site Of Adipose Explant Collection And CLmentioning
confidence: 99%
“…Neck circumference has been proposed as an indicator of upper body fatness [10,11], as it has been associated with overweight and obesity phenotypes [12][13][14][15] as well as with cardiovascular disease risk factors [16][17][18][19][20]. Neck circumference is considered a practical measurement because, unlike other methods, it is easy to measure, it does not vary during the course of the day, it does not change with food intake or abdominal distension, it is not altered by inhalation or exhalation, and it can be measured without having to remove clothing [21,22].…”
Section: Introductionmentioning
confidence: 99%